Comparative Studies of Bacillus thuringiensis var. israelensis Metabolism in Different Concentrations of Cassava Flour Processing Waste Based Media - Ernandes, Samara (2014)
Techniques of production of enthomopatogenic bacteria are developed aiming to increase the productivity and to reduce the costs of the fermentative process. Like this, it has been using agroindustrial wastes or by-products as nutrient sources in culture medium, having been used, in this study, the manipueira, a by-product of the processing of the cassava flour. Fermentations were performed in flasks of Erlenmeyer of 500 mL containing 250 mL of culture media, conditioned in shaker at 180 r.p.m. and 28°C, and the media were composed by manipueira, in concentrations that varied between 400 and 1000 mL/L. The time of the process varied between 48 and 120 hours. They appraised the following parameters: cellular growth, the production of spores, the reduction of organic matter (COD analysis) and the variation of reduction sugar. Although there was a proportional cellular growth to the manipueira concentration, the production of spores was similar in all the cases, at the end of the process, in spite of the smallest speed of production of the same ones in the highest concentrations. In relation to the variation of COD, it has, also, a percentile minor of reduction in the highest concentrations. In the analysis of variation of reduction sugars, the higher concentrations are the ones that they present larger slowness in the reduction of this.